2016
DOI: 10.1007/s11357-016-9950-x
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoproteins and HDL cholesterol do not associate with the risk of future dementia and Alzheimer’s disease: the National Finnish population study (FINRISK)

Abstract: Data on associations of apolipoproteins A-I and B (apo A-I, apo B) and HDL cholesterol (HDL-C) with dementia and Alzheimer's disease (AD) are conflicting. Our aim was to examine, whether apo B, apoA-I, their ratio, or HDL-C are significant, independent predictors of incident dementia and AD in the general population free of dementia at baseline. We analyzed the results from two Finnish prospective population-based cohort studies in a total of 13,275 subjects aged 25 to 74 years with mainly Caucasian ethnicity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
28
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 41 publications
9
28
6
Order By: Relevance
“…Notably, the direction of the association between HDL-C and AD risk differed from that reported in previous observational studies [26,27] and guidelines. A recent meta-analysis reported no signi cant association between HDL-C and AD risk [23].…”
Section: Discussioncontrasting
confidence: 78%
“…Notably, the direction of the association between HDL-C and AD risk differed from that reported in previous observational studies [26,27] and guidelines. A recent meta-analysis reported no signi cant association between HDL-C and AD risk [23].…”
Section: Discussioncontrasting
confidence: 78%
“…In contrast, in a National Finnish prospective population study including 13,275 subjects (age 25–74 years), HDL‐C levels were inversely associated with AD risk when adjusted for competing risks. However, this result did not provide clinical relevance to support the application of lipid as predictive marker of incident dementia …”
Section: Role Of Hdls In Neurological Diseasesmentioning
confidence: 66%
“…However, this result did not provide clinical relevance to support the application of lipid as predictive marker of incident dementia. 141 It has been shown that apoA-I obtained from the plasma macrophages of AD patients is less efficient in ABCA1 dependent cholesterol reversing transport compared to normal, suggesting alterations in the interaction between the apoA-I and the ABCA1. 135 Moreover, apoE-ε4 and apoJ are major susceptibility genes for AD 142 and have been associated with sporadic AD and familial late onset AD, as well as being a strong predictor of clinical progression in MCI.…”
Section: Dementiamentioning
confidence: 99%
“…A Swedish twin study (n=60) found that higher ApoB at baseline predicted dementia at least 3 years later, although any cause of dementia was included in this small study [53]. A pooled analysis of two Finnish prospective population-based cohort studies (n=13,275) found that baseline ApoB was not associated with incident AD or dementia 10 years later [54]. At present, the role of ApoB in the development of SVD or VaD is unclear.…”
Section: Lipid Effects On Vascular Dementiamentioning
confidence: 89%